Strategi Guru Dalam Peningkatan Mutu Pembelajaran Etika Hindu - Ida Bagus Alit Arta Wiguna; Komang Ayu Tri Ratna Dewi (UHN IGB Sugriwa Denpasar, 2020)
Ethics is the basic framework of learning Hinduism. The decline in the ethics of the Hindu youth generation can be overcome from an educational aspect. The purpose of this research to determine the teacher's strategy in implementing Hindu Ethics in Hindu Religion learning. This research uses qualitative research. Data collection methods used in this research are methods such as (1) observation, (2) interviews, (3) documentation. After the data is collected, the data is processed with descriptive data in the following steps: 1) argumentative inductive technique through the description process - categorization - specifications (details of classification) then go from the specific facts inductively to conclusions, (2) Classification and (3) Interpretation. Data description is done through interviews, observations, and documents in writing. This research was conducted in class XI as many as 12 classes and the number of students consisted of 450 people, but the focus of this research was in class XI IPS 3, where IPS students were known for their lack of good ethics towards teachers in the teaching and learning process which consisted of 39 students. The Hindu Ethics Learning Strategy in class XI SMA Negeri 7 Denpasar is carried out in a structured manner, starting from preliminary activities including apperception which is a stepping stone given to the teacher to motivate students in the Hindu Ethics learning process so that students have attitudes by the teachings of Ahimsa and Satya. The core activities include observing, questioning, gathering, associating, or processing information and communicating the results. The final activity, namely the teacher provides an assessment of students to determine the level of student understanding of the material given.